The Influence of Transparency, Governance, and Financial Accountability in Managing Financial Reporting in the Public Sector - Rizki Inmas Pratiwi; Hali ah; Andi Kusumawati (International Journal of Educational and Life Sciences, 2024)
Transparency, good governance and effective financial accountability are key pillars in the management of financial statements in the public sector. Transparency allows stakeholders to access financial information clearly, which in turn increases accountability and public trust. Good governance refers to the application of the principles of accountability, participation and efficiency in financial management. Meanwhile, financial accountability is the basis for ensuring that every use of public resources is properly accounted for and according to the rules. This study aims to analyze the effect of transparency, governance and financial accountability in the public sector. In this study, researchers used a qualitative descriptive method, namely a literature review, whose literature review used secondary data, namely articles / journals of previous researchers accessed from google scholer. From the results of this study transparency, governance and financial accountability in the management of financial reporting in the public sector show that these three elements significantly improve the quality of financial reporting. transparency can facilitate access to information, governance can strengthen internal control and supervision and accountability can ensure accountability for budget use.